2016
DOI: 10.1002/anie.201601935
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Confined in the Interlayer Region of Birnessite: an Active Electrocatalyst for Water Oxidation

Abstract: We report a synthetic method to enhance the electrocatalytic activity of birnessite for the oxygen evolution reaction (OER) by intercalating Ni(2+) ions into the interlayer region. Electrocatalytic studies showed that nickel (7.7 atomic %)-intercalated birnessite exhibits an overpotential (η) of 400 mV for OER at an anodic current of 10 mA cm(-2) . This η is significantly lower than the η values for birnessite (η≈700 mV) and the active OER catalyst β-Ni(OH)2 (η≈550 mV). Molecular dynamics simulations suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
109
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 28 publications
9
109
1
Order By: Relevance
“…Typically,h igher Ta fel slopes ( % 120 mV dec À1 )a re associated with water adsorption on the catalytic site as the rate-determining step, whereas lower Ta fel slopes( % 40 mV dec À1 )s uggest OÀOb ond formation as the rate-determining step. [49] Therefore, both water adsorption and OÀOf ormation are ratedetermining step for (Ni 0.87 Fe 0.13 ) 2 P-Ni and RuO 2 in the high-potential region, [50] and might be influenced by the reactions in low-potential region, leading to the different Tafel slopes.…”
Section: Resultsmentioning
confidence: 99%
“…Typically,h igher Ta fel slopes ( % 120 mV dec À1 )a re associated with water adsorption on the catalytic site as the rate-determining step, whereas lower Ta fel slopes( % 40 mV dec À1 )s uggest OÀOb ond formation as the rate-determining step. [49] Therefore, both water adsorption and OÀOf ormation are ratedetermining step for (Ni 0.87 Fe 0.13 ) 2 P-Ni and RuO 2 in the high-potential region, [50] and might be influenced by the reactions in low-potential region, leading to the different Tafel slopes.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that disturbance of abirnessite structure by doping it with other 3d transitionm etals can enhance the catalytic activity of the material. [41][42][43] Such as tructural disturbancem ight also be reached by aj udicious choice of the parameters in the electrodeposition process. However,e xamination of the spatialphase distribution and/or structural distortions is beyond the capabilities of the specific experimental technique used herein-consequentlys uggesting ap romising area for future study.…”
Section: Resultsmentioning
confidence: 99%
“…031-0.061 s À1 )m aterials revealed highera ctivity for OER than birnessite (TOF = 0.0004 s À1 )u nder the same experimental conditions. [128][129][130] Based on the structural similarity of the compounds,i tw as suggestedt hat water oxidation mainly occurs in the interlayer region of the birnessite composites.…”
Section: Heterogeneous Catalysts For Oermentioning
confidence: 99%